PENENTUAN NILAI KALORI DETRITUS HUTAN MANGROVE DENGAN MENGGUNAKAN BOMB CALORIMETER - Andi, Pos; ', Sugianto; Emrinaldi, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted to determine a calorie quality of mangrove detritus using Bomb Calorimeter. The measurements were carried out in order to measure the physical parameters, such as water content, concentration of ash, amount of sulfur, and calorie content. Each sampel was treated on the same pressure and volume. The sampleswere taken from Dumai city on five different regions. Quality test to the samples resulted calorie content of 4.185 cal/g, the degree of water of 14,29 %, the degree of ash of 4.48 % and the amount of sulfur of 0,03 % for sample of point A. Meanwhile for point B, C, D, and E, the value of calorie content, degree of water, degree of ash, and degree of sulfur were 4.195 cal/g, 4.139 cal/g, 4.164 cal/g, and 4.002 cal/g, 13,90 %, 14,30 %, 13,10 %, and 13, 80 %, 4,84 %, 5,45 %, 4,59 %, and 6,10 %, and 0,11 %, 0,11 %, 0,15 %, and 0,19 %, respectively . Among the four physical parameters, calorie content is the most important parameter to indicate the quality of detritus of mangrove. Based on the obtained data, the sample of point B was the best sample because of its highest calorie content compared to the other samples.